Improving the Efficacy of Antimicrobials against Biofilm-Embedded Bacteria Using Bovine Hyaluronidase Azoximer (Longidaza®) - Elena Trizna; Diana Baidamshina; Anna Gorshkova; Valentin Drucker; Mikhail Bogachev; Anton Tikhonov; Airat Kayumov (MDPI AG, 2021)
While in a biofilm, bacteria are extremely resistant to both antimicrobials and the immune system, leading to the development of chronic infection. Here, we show that bovine hyaluronidase fused with a copolymer of 1,4-ethylenepiperazine N-oxide and (N-carboxymethyl) -1,4-ethylenepiperazinium bromide (Longidaza®) destroys both mono- and dual-species biofilms formed by various bacteria. After 4 h of treatment with 750 units of the enzyme, the residual biofilms of Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae preserved about 50-70% of their initial mass. Biomasses of dual-species biofilms formed by S. aureus and the four latter species were reduced 1.5-fold after 24 h treatment, while the significant destruction of S. aureus-P. aeruginosa and S. aureus-K. pneumoniae was also observed after 4 h of treatment with Longidaza®. Furthermore, when applied in combination, Longidaza® increased the efficacy of various antimicrobials against biofilm-embedded bacteria, although with various increase-factor values depending on both the bacterial species and antimicrobials chosen. Taken together, our data indicate that Longidaza® destroys the biofilm structure, facilitating the penetration of antimicrobials through the biofilm, and in this way improving their efficacy, lowering the required dose and thus also potentially reducing the associated side effects.